PENDAMPINGAN PELAKSANAAN PEMBELAJARAN BERBASIS BAHASA IBU DI TKK OLAEWA KECAMATAN BOAWAE KABUPATEN NAGEKEO - Efrida Ita (STKIP Citra Bakti, 2022)
It has been identified that children use their mother tongue in their daily lives. This is not surprising because mother tongue is the first language that is known and used by children to communicate. This intense communication using the mother tongue causes children to have difficulty understanding the material when participating in the learning process at school. Because the language of instruction used in schools is Indonesian. This problem is a serious concern for schools so that schools can use their mother tongue as the language of instruction in order to help children more easily understand the material presented by the teacher. The purpose of this service activity is to assist teachers in the implementation of mother tongue-based learning. The method of implementing the service is through monitoring and evaluation method, observation, and face-to-face discussions. This service activity was carried out at Olaewa Kindergarten as one of the target schools for using mother tongue in learning activities. The results of the mentoring activities are that children are more actively involved in playing and learning activities and create learning situations that are interactive, fun and stimulate learning motivation for children.